2018
DOI: 10.1021/acsnano.8b01308
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Established Tumors by Chemically Self-Assembled Nanoring Labeled T Cells

Abstract: Our laboratory has developed chemically self-assembled nanorings (CSANs) as prosthetic antigen receptors (PARs) for the nongenetic modification of T cell surfaces. PARs have been successfully employed in vitro to activate T cells for the selective killing of leukemia cells. However, PAR efficacy has yet to be evaluated in vivo or against solid tumors. Therefore, we developed bispecific PARs that selectively target the human CD3 receptor and human epithelial cell adhesion molecule (EpCAM), which is overexpresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 66 publications
12
49
0
Order By: Relevance
“…SEC and DLS results were consistent with our previous analyses of Fn3-targeted CSANs, including cryo-electron microscopy (cryo-EM) evidence of nanoring formation. 43, 44…”
Section: Methodsmentioning
confidence: 99%
“…SEC and DLS results were consistent with our previous analyses of Fn3-targeted CSANs, including cryo-electron microscopy (cryo-EM) evidence of nanoring formation. 43, 44…”
Section: Methodsmentioning
confidence: 99%
“…The enhanced avidity of the rings provides enhanced binding and selectivity to T cells and the targeted antigen of interest (28). We have successfully demonstrated the in vitro and in vivo efficacy of scFv-based PARs (26,29). However, generating scFv-based monomers to form the rings is dependent on refolding steps that increases the time required for purification with significantly reduced protein yields (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biologically derived nanobiomaterials, such as cancer cell membranes, viral proteins, and DNAs, have started to be used for new cancer nanovaccines [ 260 263 ]. Researchers found that tumor antigens and subcellular particles in the cancer membrane, such as melanoma cells, could be loaded into various NPs, which induce specific cellular and humoral responses, thus preventing tumor growth [ 157 , 264 , 265 ].…”
Section: Novel Biomaterials For Cancer Immunotherapymentioning
confidence: 99%